PENGERTIAN TUHAN PERSFEKTIF SUNNI DAN SYIAH STUDI KAJIAN HADIS - A. Rido Iqtaro; Muhammad Hiysam Bin Mustafa; Fadel Muhammad Iqbal; Muhammad Nurul Mustaqim; Faisal Haitomi (Journal Khafi : Journal Of Islamic Studies, 2023)
The approach to respond to the difference in views between Sunnis and Shiites about the meaning of God in their respective eyes. Correlating the two through their hadiths, can involve an in-depth understanding of the history, classification, parameters, and criteria for the validity of hadith in the two major schools of Islam. The striking differences between Sunnis and Shia include the Prophet's position as a source of hadith, the distribution of hadith, justice, and the credibility of the Companions. Sunnis consider the sahih hadith sanad to be uninterrupted from the narrator to the Messenger, while the Shia view the sahih hadith sanad when it is connected to the Messenger or Imam Ma'sum without being interrupted. In addition, Sunnis believe that all companions are fair, while Shiites have different views. To correlate the views of Sunnis and Shiites through their hadith, a careful and careful approach may be required. This can involve an in-depth analysis of the hadith recognized by both schools, such as.